Gastric foregut cystic developmental malformation: Case series and literature review - Geng, Yan-Hua (World J Gastroenterol, 2015)
Foregut cystic developmental malformation (FCDM) is a very rare lesion of the alimentary tract, especially in the stomach. We discuss the concepts of gastric duplication cyst, bronchogenic cysts, and FCDM. Nomenclature has been inconsistent and confusing, but, by some definitions, gastric duplication cysts involve gastric mucosa and submucosal glands, bronchogenic cysts involve respiratory mucosa with underlying cartilage and glands, and FCDM lacks gastric mucosa or underlying glands or cartilage but has pseudostratified ciliated columnar epithelium (PCCE). We searched our departmental case files from the past 15 years and identified 12 cases of FCDM in the alimentary tract. We summarize the features of these 12 cases including a report in detail on a 52-year-old man with a submucosal cyst lined with simple PCCE and irregular and stratified circular muscle layers that merged with gastric smooth muscle bundles near the lesser curvature of the gastric cardia. A literature review of cases with this histology yielded 25 cases. We propose the term gastric-FCDM for such cases. Our own series of 12 cases confirms that preoperative recognition of the entity is infrequent and problematic. The rarity of this developmental disorder, as well as a lack of understanding of its embryologic origins, may contribute to missing the diagnosis. Not appreciating the diagnosis preoperatively can lead to an inappropriate surgical approach. In contrast, presurgical recognition of the entity will contribute to a good outcome and reduced risk of complications.